Analisis Faktor-Faktor Yang Menurunkan Pendapatan Pedagang Pasar Tradisional Petisah Kota Medan - Ihsan Nasution, Ahmad Fikri; Lubis, Fauzi Arif; Jannah, Nurul (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to determine the factors that affect the decline in the income of traditional market traders petisah. This study was conducted using a qualitative research approach. Researchers used data collection techniques such as interviews and SOAR analysis to find strategies. Petisah market is one of the largest markets in the city of Medan and is the second largest market after the Central Market of medan or central market that has been under the auspices of the market PUD. Almost all traditional markets in Indonesia are still struggling with internal market problems such as poor market management, very mini market facilities and infrastructure. Traditional markets as a cash cow for the receipt of retribution, the proliferation of street vendors who reduce customers market traders, and the lack of capital assistance available to traditional traders. This research data obtained from primary data with data collection techniques used are interviews, observations, and documentation. The results of this study showed that there are 2 factors that reduce the income of traders, the first is internal factors or factors of problems in the market, the second is external factors or factors of problems that come from outside the market.